2000
DOI: 10.1002/(sici)1097-0231(20000530)14:10<829::aid-rcm951>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of matrix-assisted laser desorption/ionization to on-line aerosol time-of-flight mass spectrometry

Abstract: Matrix-assisted laser desorption/ionization (MALDI) mass spectra were obtained from single biological aerosol particles using an aerosol time-of-flight mass spectrometer (ATOFMS). The inlet to the ATOFMS was coupled with an evaporation/condensation flow cell that allowed the aerosol to be coated with matrix material as the sampled stream entered the spectrometer. Mass spectra were generated from aerosol composed either of gramicidin-S or erythromycin, two small biological molecules, or from aerosolised spores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 20 publications
2
104
0
Order By: Relevance
“…10,11,21) Stowers et al 10) reported the on-line aerosol MALDI MS analysis of Bacillus atrophaeus spores and found a reproducible peak at a mass of 1224 Dalton, which was attributed to a part of peptidoglycan. The work done by Van Wuijckhuijse 11,21) included the on-line aerosol MALDI analysis of spores of Bacillus atrophaeus and of vegetative cells of Escherichia coli.…”
Section: Single Particle Mass Spectrometry Bioaerosol Analysis By Malmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,21) Stowers et al 10) reported the on-line aerosol MALDI MS analysis of Bacillus atrophaeus spores and found a reproducible peak at a mass of 1224 Dalton, which was attributed to a part of peptidoglycan. The work done by Van Wuijckhuijse 11,21) included the on-line aerosol MALDI analysis of spores of Bacillus atrophaeus and of vegetative cells of Escherichia coli.…”
Section: Single Particle Mass Spectrometry Bioaerosol Analysis By Malmentioning
confidence: 99%
“…Software to acquire and process the data of the instrument was also developed by Weiss 7) . Stowers et al 10) and Van Wuijckhuijse 11) implemented MALDI mass spectrometry, a technique that al-…”
Section: Introductionmentioning
confidence: 99%
“…Single particle MALDI experiments provide a suitable system to access the performance of the instrument [5][6][7]. Gramicidin S particles were generated from a 50/50 H 2 O/ethanol solution of 2,5-dihydroxybenzoic acid (DHB; 3 ϫ 10 Ϫ3 M) and gramicidin S at a 100:1 matrixto-analyte molar ratio.…”
Section: Particle Generation and Samplingmentioning
confidence: 99%
“…In 2005, Harris et al described aerosol MALDI in an ion trap mass spectrometer [36]. A number of groups have analyzed proteins, but in 2000, Stowers et al were the first to analyze Bacillus spores [37,38]. Regardless of the analyte, aerosol MALDI differs from classical bulk MALDI in a number of important ways.…”
mentioning
confidence: 99%